The Limits of Human Will: Analyzing Nature and Survival in To Build a Fire by Jack London - Izkha Primadani Aji; Henrikus Joko Yulianto (Universitas Islam Negeri Palopo, 2026)
This study examines the representation of nature and human survival in Jack London’s To Build a Fire from an ecocritical perspective. It aims to analyze how nature is portrayed as a dominant ecological force and how the protagonist’s anthropocentric mindset contributes to his failure. The study employs a qualitative descriptive approach, using close reading to analyze textual data from the short story within an ecocritical framework. The findings show that nature is represented as an autonomous and unchanging force that operates independently of human intention. The extreme environmental conditions highlight the vulnerability of the human body and the limitations of rational decision-making. The protagonist’s confidence in logic reflects an anthropocentric perspective that underestimates ecological power. His repeated attempts to control the environment ultimately fail, demonstrating the inability of human will to overcome natural forces. This study contributes to contemporary ecocritical discourse by demonstrating how survival narratives challenge anthropocentric perspectives and promote ecological awareness through literary representation. This study concludes that the story critiques human-centered assumptions and emphasizes the dominance of nature over human life. It reinforces the idea that humans are subject to ecological systems beyond their control, contributing to discussions on environmental awareness in literary studies.